Factor Determinant Profitability and Financial Distress of Non-Financial Sector Companies in Indonesia - Agustin, Happyta; Bertuah, Eka (Owner : Riset dan Jurnal Akuntansi, 2024)
This study aims to examine the determinants of financial distress of non-financial sector companies in Indonesia during the Covid 19 pandemic and test whether company profitability can mediate financial performance on the possibility of financial distress. The sampling technique was purposive sampling, namely non-financial sector companies that experienced negative operating profit during 2020 and 2021. The analysis technique used is panel data regression analysis. The results showed that sales growth has a positive impact on profitability and DER has a negative impact on profitability. While TATO has a positive effect on Financial Distress. This study also shows that profitability cannot mediate financial performance on financial distress. This study contributes to the testing of signalling theory, where information on sales growth and corporate capital structure affects the company's profitability. In addition the company's very limited ability to manage its assets during Covid 19 conditions affects the possibility of financial distress.